2016
DOI: 10.3390/rs8030166
|View full text |Cite
|
Sign up to set email alerts
|

First Experience with Sentinel-2 Data for Crop and Tree Species Classifications in Central Europe

Abstract: Abstract:The study presents the preliminary results of two classification exercises assessing the capabilities of pre-operational (August 2015) Sentinel-2 (S2) data for mapping crop types and tree species. In the first case study, an S2 image was used to map six summer crop species in Lower Austria as well as winter crops/bare soil. Crop type maps are needed to account for crop-specific water use and for agricultural statistics. Crop type information is also useful to parametrize crop growth models for yield e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
469
3
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 734 publications
(595 citation statements)
references
References 62 publications
35
469
3
23
Order By: Relevance
“…Considering maize and sugar beet alone only confirmed the SWIR band while Red-Edge 2 and 3 outperformed Red-Edge 1. Differences might be due to differences in the crop types of interest; crop classification results from Immitzer et al [16] were mainly driven by winter wheat and maize, which suggests that different spectral bands enhance different pairwise comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering maize and sugar beet alone only confirmed the SWIR band while Red-Edge 2 and 3 outperformed Red-Edge 1. Differences might be due to differences in the crop types of interest; crop classification results from Immitzer et al [16] were mainly driven by winter wheat and maize, which suggests that different spectral bands enhance different pairwise comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…For crop and tree type identification, Immitzer et al [16] underlined the importance of Red-Edge 1, Blue and SWIR bands. Considering maize and sugar beet alone only confirmed the SWIR band while Red-Edge 2 and 3 outperformed Red-Edge 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we applied VHR RapidEye data comprising a red edge channel that was centered at 710 nm. Recent studies have shown the performance of red edge bands in facilitating important information on the state of vegetation and their benefit for vegetation monitoring [29][30][31]. In 2015, Sentinel-2A satellite has been launched.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, crop mapping based on satellite data desperately requires high-quality spatial and temporal data, particularly in China where agricultural landscapes are complex with a diversity of cropping systems and small field sizes [18]. New sensors, such as Chinese GaoFen and overseas Sentinel-2A sensor, were designed for data enhancement to offer unprecedented perspectives on land cover/use and vegetation [19][20][21][22]. These new missions revisit the same area more frequently (every four or ten days) [23,24].…”
Section: Introductionmentioning
confidence: 99%